Biokinetics of ultrafine gold nanoparticles (AuNPs) relating to redistribution and urinary excretion: a long-term in vivo study. (13th September 2016) - Naz, Farhat; Koul, Veena; Srivastava, Amita; Gupta, Yogendra Kumar; Dinda, Amit Kumar
Abstract: Gold nanoparticles (AuNPs) of ultrafine size have drawn attention for their use in drug delivery systems. Tissue toxicity may be an issue when AuNPs are used for such applications. We investigated the long-term biokinetics (90 d), redistribution, and urinary excretion of three different-sized (2 ± 0.5 nm, 5 ± 1 nm, and 10 ± 2 nm) AuNPs after a single intravenous (i.v.) administration of 1250 µg/kg dose in mice. ICP-AES analysis of lungs, liver, spleen, heart, kidney, brain, blood, and urine revealed highest accumulation of gold in spleen around 15 d after injection. A low concentration was detected in brain after 1 d without any residual AuNPs after 30 d. Ultrastructural study of brain tissue also showed few AuNPs in lysosome with no changes in cellular architecture. Renal retention of AuNPs was limited indicating low nephrotoxic potential. AuNPs were detectable in urine till 30 d after single injection indicating slow excretion from the body. No evidence of significant toxicity was observed in hemogram, serum biochemistry, and tissue histology. No mortality, changes in behavior, hair color, weight, and food intake was observed as compared to control mice. Therefore, we conclude that the ultrafine AuNPs are predominantly excreted in urine without any systemic toxicity following i.v. administration and are hence safe for use in drug delivery systems.